2022
DOI: 10.1038/s41467-022-30332-5
|View full text |Cite
|
Sign up to set email alerts
|

Limiting motorboat noise on coral reefs boosts fish reproductive success

Abstract: Anthropogenic noise impacts are pervasive across taxa, ecosystems and the world. Here, we experimentally test the hypothesis that protecting vulnerable habitats from noise pollution can improve animal reproductive success. Using a season-long field manipulation with an established model system on the Great Barrier Reef, we demonstrate that limiting motorboat activity on reefs leads to the survival of more fish offspring compared to reefs experiencing busy motorboat traffic. A complementary laboratory experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…However, no previous studies were conducted on crustaceans to test the effect of anthropogenic sound on behaviors that involve a direct impact on fitness, such as maternal care with important consequences in the offspring survival. In contrast, the effect of noise on parental care behavior was demonstrated in fishes (Picciulin et al, 2010;Nedelec et al, 2016;Nedelec et al, 2017;McCloskey et al, 2020;Nedelec et al, 2022).…”
Section: Introductionmentioning
confidence: 87%
“…However, no previous studies were conducted on crustaceans to test the effect of anthropogenic sound on behaviors that involve a direct impact on fitness, such as maternal care with important consequences in the offspring survival. In contrast, the effect of noise on parental care behavior was demonstrated in fishes (Picciulin et al, 2010;Nedelec et al, 2016;Nedelec et al, 2017;McCloskey et al, 2020;Nedelec et al, 2022).…”
Section: Introductionmentioning
confidence: 87%
“…The few studies that investigated this have shown mixed results. While white-crowned sparrows (Zonotrichia leucophrys) reverted back to low frequency songs (Derryberry et al, 2020) and spiny chromis (Acanthochromis polyacanthus) larvae had increased survival rates (Nedelec et al, 2022) in quieted conditions, juniper and pinyon seedling recruitment did not recover following the removal of noise (Phillips et al, 2021). The persistence of effects might depend on the time it takes for the effect to reverse, as well as the behavioral plasticity of the affected species.…”
Section: Future Directionsmentioning
confidence: 99%
“…site occupancy, territorial and reproductive behaviour, and stress metabolism) and species interactions (e.g. through feeding efficiency or hiding tendency) that can ultimately affect population dynamics and community composition [4,5]. Accordingly, noise pollution is causing an 'acoustic climate change', likely to alter ecosystem functioning [6,7] and, as such, is gaining increased attention among resource managers and policy makers [8][9][10][11].…”
Section: Noise Pollution Can Affect Wildlife Diseases Through Impacts...mentioning
confidence: 99%
“…Cavitation can reduce survival of free-living parasite stages [56,57], although, the role of cavitation sound in this is not yet investigated. Nevertheless, pistol shrimps are able to stun their tiny aquatic prey by cavitation sound [58], and there are multiple studies on zooplankton, which report reduced survival [59], retarded development, and higher rates of malformations [5,60] through noise impacts.…”
Section: Noise Impacts On Parasite Exposure Patternsmentioning
confidence: 99%
See 1 more Smart Citation